Methodologies for investigating performance changes with supplement use - Burke, M. L.; Peeling, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Many expert sporting bodies now support a pragmatic acceptance of the use of performance supplements which have passed a risk:benefit analysis of being safe, effective, and permitted for use, while also being appropriate to the athlete`s age and maturation in their sport. However, gaining evidence of the performance benefits of these supplements is a process challenged by the scarcity of research in relation to the number of available products, and the limitations of the poor quality of some studies. While meta-analyses and systematic reviews can help to provide information about the general use of performance supplements, the controlled scientific trial provides the basis on which these reviews are undertaken, as well as an opportunity to address more specific questions about supplement applications. Guidelines for the design of studies include the choice of well-trained athletes who are familiarized with performance tasks that have been chosen on their basis of their known reliability and validity. Supplement protocols should be chosen to maximize the likely benefits, and researchers should also make efforts to control confounding variables, while keeping conditions similar to real-life practices. Performance changes should be interpreted in light of what is meaningful to the outcomes of sporting competition. Issues that have been poorly addressed to date include the use of several supplements in combination and the use of the same supplement over successive events, both within a single, and across multiple competition days. Strategies to isolate and explain the variability of benefits to individuals are also a topic for future investigation.